Islam and Democracy at the Fringes of Europe: The Role of Useful Historical Legacies. Issue 2 (June 2015) - Elbasani, Arolda
Abstract: This article analyzes how the Muslim majority has engaged with, and contributed to parallel processes of democratization and European integration in post-Communist Albania. The assessment of Muslims' choices focuses on the Central organization, the Albanian Muslim Community, which is recognized by the state as the only authority in charge of all the administrative and spiritual issues pertinent to the community of Sunni believers, and serves as the main hub of respective religious activities in the country. The analysis of democratization, and Muslims' respective choices, are divided into two different periods, namely democratic transition (1990–1998) and democratic consolidation (1998–2013), each facing democratizing actors, including Muslim groups, with different challenges and issues. We argue that the existence of a useful pool of arguments from the past, the so-called Albanian tradition, has enabled Muslims to contravene controversial foreign influences and recast Islam in line with the democratic and European ideals of the Albanian post-communist polity. This set of historical legacies and arguments explain Muslims' similar positioning toward democracy throughout different stages marked by different institutional restrictions and state policies.